ANALISIS YURIDIS PENGATURAN JANGKA WAKTU PELIMPAHAN BERKAS PERKARA DARI PENYIDIK KEPADA PENUNTUT UMUM DIKAITKAN DENGAN PENETAPAN STATUS TERSANGKA BERDASARKAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA - Markus, Freddy; Indra, Mexsasai; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
When initiating the investigation process, the investigator must immediately fulfill the two evidences set out in Article 184 of the Criminal Procedure Code and establish the suspect in a crime and complete the file to be immediately delegated to the prosecutor. For suspects detained investigators have a time limit to settle the case while for suspects who are not detained investigators have no time limit to complete the case and may be constrained or lasted for years. This is of course detrimental to the right of the suspect to be immediately examined in court and obtain legal certainty regarding his status. The purpose of writing this thesis, namely: First, to determine the time period of determination of suspect status by the investigator. Second, to know the ideal period of time for the determination of suspect status.The type of research used is a normative legal research or can be called also the research of doctrinal law, normative legal research is a literature law research. Sources of data in this normative legal research is the data or material law of primary, secondary, and tertiary. The author in preparing and analyzing all the data and materials obtained in this study, conducted qualitatively. From the results of research problems there are two main things that can be concluded. First, the timing of the determination of suspect status by the investigator has not been clearly and completely regulated. Secondly, according to the author of the ideal period of time regarding the determination of suspect status in the investigation process, especially for the suspect who is not detained that is 90 days in accordance with the provisions in Article 88 of the Draft Law on Criminal Procedure Code. Author's suggestion, Firstly, it is necessary to amend the current Criminal Procedure Code, specifically in Article 50, concerning the time limit of the investigation process. Secondly, the Government needs to enact the New Criminal Procedure Code which has been prepared especially in Article 88 which regulates the time period for investigation process for the non-detained suspect that is 90 days to protect the rights of the suspect.Keywords : Unification Period, Investigation, Suspect, Legal Certaint